Высокочувствительный СВЧ измеритель влагосодержания в неполярных диэлектрических жидкостях на основе ступенчатого неоднородного коаксиального резонатора - Рудаков, Валерий Васильевич; Коробко, Александр Анатольевич (НТУ "ХПИ", 2016)
Рассматривается высокочувствительный измеритель влагосодержания в неполярных жидких диэлектриках. Аргументированы пути повышения чувствительности классического диэлькометрического метода. Приводится описание разработанной конструкции измерителя влажности на основе ступенчатого неоднородного коаксиального резонатора. Рассмотрены результаты анализа резонансных характеристик измерительного преобразователя, а также определены величины объемного влагосодержания смесей трансформаторное масло – вода в диапазоне влагосодержания (10–10⁴) cм³/м³.

Purpose. Objective is to create a moisture meter for non-polar liquid dielectrics with low volumetric moisture content of more than 10⁻³ %. Methodology. Moisture measuring is based on dielcometric method. It is implemented as a resonant method of determining a capacitance measuring transducer. Measuring transducer capacitive type has a working and parasitic capacitance. It was suggested the definition of moisture on four of resonance frequencies: when the measuring transducer is turned off, one by one filled with air, "dry" and investigated liquid, to determine the parasitic capacitance of the measuring generator, and the parasitic capacitance of the measuring transducer and humidity. Measurement frequency was increased up to microwave range to increase the sensitivity. Measuring transducer with distributed parameters representing a step heterogeneous coaxial resonator is used by. This measuring transducer has a zero stray capacitance, because the potential electrode has a galvanic connection with an external coaxial electrode. Inductive ties loop is used to neglect parasitic capacitance of the measuring generator, and to increase the quality factor of the system. Measuring moisture is reduced to measuring the two frequencies of resonance frequency and "dry" and investigated liquid. Resonant characteristics transducer in a step inhomogeneous coaxial resonator have been investigated to determine the quality factor of filled with air and transformer oil, and experiments to measure the moisture content in transformer oil have been conducted. Results. Measuring transducer of distributed type is developed and researched – it is step inhomogeneous coaxial resonator. It has a smaller geometric length and larger scatter of the first and second resonant frequencies. Expression is obtained for determination of moisture on the basis of two resonant frequencies. The formula of the two frequencies to determine the moisture is correct. Resonant characteristics are obtained for measuring transducer. Its quality factor has been determined – it does not depend on what it is filled with air or oil. The moisture content in transformer oil for the amount of water to 10⁻³ % with an error of no more than 6.7 % has been determined. Originality. It has been proposed to use of an inhomogeneous step coaxial resonator as a measuring transducer. Original high sensitive moisture meter for the fluid at rest and flowing fluid with low values of parasitic capacitances has been developed and researched. An original method of determining the moisture by measuring the two frequencies of resonance has been proposed and implemented. Practical value. This meter may be used to determine moisture in any of the non-polar liquid with high speed and accuracy. Moisture meter can be used in electrical engineering, aeronautical engineering, in the chemical and food industries.
A high sensitive microwave measuring device of the moisture content in the non-polar dielectric liquids based on an inhomogeneous step coaxial resonator
Keywords: измеритель влагосодержания; жидкие неполярные диэлектрики; измерительный преобразователь; ступенчатый коаксиальный неоднородный резонатор; измерительный генератор; резонасные характеристики; объемное влагосодержание; трансформаторное масло; moisture meter; non-polar liquid dielectrics; measuring transducer; step inhomogeneous coaxial resonator; measuring generator; resonance characteristics; volumetric water content; transformer oil